A minireview of 1, 2, 3‐triazole hybrids with O‐heterocycles as leads in medicinal chemistry. (11th October 2021) - Saroha, Bhavna; Kumar, Gourav; Kumar, Ramesh; Kumari, Meena; Kumar, Suresh
Abstract: Over the past few decades, the dynamic progress in the synthesis and screening of heterocyclic compounds against various targets has made a significant contribution in the field of medicinal chemistry. Among the wide array of heterocyclic compounds, triazole moiety has attracted the attention of researchers owing to its vast therapeutic potential and easy preparation via copper and ruthenium‐catalyzed azide‐alkyne cycloaddition reactions. Triazole skeletons are found as major structural components in a different class of drugs possessing diverse pharmacological profiles including anti‐cancer, anti‐bacterial, anti‐fungal, anti‐viral, anti‐oxidant, anti‐inflammatory, anti‐diabetic, anti‐tubercular, and anti‐depressant among various others. Furthermore, in the past few years, a significantly large number of triazole hybrids were synthesized with various heterocyclic moieties in order to gain the added advantage of the improved pharmacological profile, overcoming the multiple drug resistance and reduced toxicity from molecular hybridization. Among these synthesized triazole hybrids, many compounds are available commercially and used for treating different infections/disorders like tazobactam and cefatrizine as potent anti‐bacterial agents while isavuconazole and ravuconazole as anti‐fungal activities to name a few. In this review, we will summarize the biological activities of various 1, 2, 3‐triazole hybrids with copious oxygen‐containing heterocycles as lead compounds in medicinal chemistry. This review will be very helpful for researchers working in the field of molecular modeling, drug design and development, and medicinal chemistry. Abstract : Triazole hybrids are the lead compound for the present‐day discoveries in medicinal chemistry. This mini‐review briefly summarizes the recently developed active hybrids of triazole with O‐heterocyclic. SAR is also discussed that set up the direction for the design and development of triazole hybrids with high efficiency against both drug‐resistant pathogens and drug sensitivity.